2019
DOI: 10.1038/s41393-019-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of adult traumatic spinal cord injury in Saint Petersburg, Russia

Abstract: Study design Retrospective population-based cohort study. Objectives To characterise the epidemiology of traumatic spinal cord injury (TSCI) among the inhabitants of Saint Petersburg, Russia. Setting All hospitals in Saint Petersburg. Methods Charts for all individuals admitted to city hospitals from 1st January 1 2012 to 31st December 2016 with acute TSCI were reviewed. Incidence rates were calculated for the whole period and for each year separately. Gender-specific and age-specific incidence rates were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
6
17
0
8
Order By: Relevance
“…It is similar to the results reported by ahoniemi and colleagues in 2008 were the most common cause of traumatic spinal injury was fall (41.2%), followed by traffic accident (39.5%) [7] . This study comes in agreement with the work of Mirzaeva and colleagues in 2019 who reported that the most frequent cause of traumatic SCI was falls (49.8%), followed by motor vehicle accidents (18.9%) [8] . On the other hand, this study comes in disagreement with the work of Pickett and colleagues in 2006 who found that the most common causes of traumatic SCI were traffic accident (35%) followed by falls (31%) [9] .…”
Section: Discussionsupporting
confidence: 93%
“…It is similar to the results reported by ahoniemi and colleagues in 2008 were the most common cause of traumatic spinal injury was fall (41.2%), followed by traffic accident (39.5%) [7] . This study comes in agreement with the work of Mirzaeva and colleagues in 2019 who reported that the most frequent cause of traumatic SCI was falls (49.8%), followed by motor vehicle accidents (18.9%) [8] . On the other hand, this study comes in disagreement with the work of Pickett and colleagues in 2006 who found that the most common causes of traumatic SCI were traffic accident (35%) followed by falls (31%) [9] .…”
Section: Discussionsupporting
confidence: 93%
“…В исследование были включены пациенты, которые достигли 18-летнего возраста, зарегистрированы на территории Санкт-Петербурга и у которых полученная травма соответствует критериям острой ПСМТ (механическое повреждение позвоночника и/или содержимого позвоночного канала (спинного мозга, его оболочек и сосудов, спинномозговых нервов)) с кодами S14, S24, S34 (по МКБ-10) [8]. Пациенты с переломами позвоночника без повреждения спинного мозга, с изолированными повреждениями нервных корешков и/или вегетативной нервной системы, а также лица, умершие на догоспитальном этапе, были исключены из исследования [6,7].…”
Section: критерии включения/исключенияunclassified
“…Потребление алкоголя было выявлено у 75 % безработных, что было значительно выше, чем среди трудоустроенных лиц (16,7 %), пенсио неров (8,3 %) и студентов (0 %). Доля безработных лиц среди когорты пациентов с ПСМТ составила 32,4 % [6], в то время как в популяции уровень безработных (согласно данным Петростата) -19,1 % [14]. Исследователи из Китая установили, что безработица является одним из факторов риска ПСМТ [13].…”
Section: результаты и их обсуждениеunclassified
See 1 more Smart Citation
“…Spinal cord injury (SCI) not only causes serious functional and family financial burdens, but also poses a series of problems for patients' mental health and social stability (1). SCI is considered to be a major public health matter worldly, and the incidence of spinal cord injury vary widely around the world.…”
Section: Introductionmentioning
confidence: 99%